Identifikasi Komposisi Tubuh Babi Timor Jantan yang Dipelihara Secara Ekstensif (IDENTIFICATION OF BODY COMPOSITION OF TIMOR LOCAL MALE PIG EXTENSIVE) - Wea, Redempta; Koten, Bernadete Barek; Koni, Theresia Nur Indah (Jurnal Veteriner; Vol 14 No 3 (2013), 2013)
The aim of this research is identifying the body composition studies timor local male pigs rearedextensively. This research has been ongoing since March to December 2011. The research  used locallytimor male pigs raised extensively with a lifespan of 2 to 3.9 months,  4 to 5.9 months, and 6 to 7.9 months.Research variable is body composition. The results showed that mean body composition: Age range 2 to 3.9months; 5100 g live weight (4200-6100 g) has carcass weight of 3778.17 g and non-carcass weight of 800.67g; Age range 4 to 5.9 months, 15 000 g  (14200-16000 g) live weight has carcass weight of 11 412 g non-carcass weight of 2088 gs and Age range 6 to 7.9 months; 18216.67 g (17500-19500 g) live weight hascarcass weight of 13876.67 g and non-carcass weight of 2520 g or the average percentage composition of thebody age range 2-7.9 months is the weight loss without the digestive tract contents of 89.93%; digestivetract contents of 5-10% average average 7.16%; carcass weight of 75.40%; non-carcass weight of 14.5%,63.70% carcass weight; weight of the head, front legs, and feet behind the 11.70% weight of edible meat andbone 60.6%, skin 3.1% and the percentage weight of the edible parts of 12.17% while the inedible parts of2.31%.
Keywords: body composition, local timor pigs, extensively